Re-evaluation of the taxonomy of the Sri Lankan pigmy shrew Suncus fellowesgordoni (Soricidae: Crocidurinae) and its phylogenetic relationship with S. etruscus - Meegaskumbura, Suyama; Meegaskumbura, Madhava; Schneider, Christopher J. (Zootaxa, 2012)
The taxonomy of the pigmy shrews Suncus fellowesgordoni and S. etruscus is unclear and their phylogenetic relationshipsare unknown. Using molecular and morphological data, we confirm the species status of S. fellowesgordoni as being dis-tinct from S. etruscus, its probable sister species. Suncus fellowesgordoni is genetically distant from S. etruscus popula-tions in Sri Lanka and India, and Europe with a percent pairwise uncorrected genetic distance of 7.9–8.2% and 9.2–9.3%for cytochrome-b (mitochondrial DNA), respectively. The genetic distance between S. fellowesgordoni and S. etruscus ofSri Lanka and India for Rag 1 (nuclear DNA, exon) is 1.3–1.7%. The two species are also morphologically distinct by S. fellowesgordoni being larger in all dimensions, darker in hue and having two denticulations on the lower incisors.